Pulmonary granulomatous reaction: talc pneumoconiosis or chronic sarcoidosis?. Issue 1 (February 1984) - Tukiainen, P; Nickels, J; Taskinen, E; Nyberg, M
Abstract : A chronic pulmonary granulomatous reaction was associated with an almost identical clinical picture in two patients exposed to talc. In both patients lung biopsy showed the deposition of talc particles and a heavy granulomatous reaction. At the time of diagnosis the Kveim test result was negative in both patients, urinary calcium excretion was normal, and there were no extrapulmonary manifestations and no response to steroid treatment. These findings point against sarcoidosis. The serum angiotensin-converting enzyme level, however, was raised in both patients. It was concluded that the patient who was exposed to talc in the rubber industry had a true talc pneumoconiosis. The other patient, who was exposed to cosmetic talcum powder, suffered from chronic sarcoidosis with talc deposition in the lungs, since an enlarged axillar lymph node containing granulomatous inflammation was discovered after two years' follow up. These cases show that it may be extremely difficult to differentiate between chronic sarcoidosis and talc pneumoconiosis even after careful clinical and histological analysis.